The Invisible Child Worker in Kenya: The Intersection of Poverty, Legislation and Culture (Nordic Journal of African Studies, 2001)
Although data on the prevalence and magnitude of child labour are inadequate, the number of children working under intolerable conditions in Kenya is estimated at over 3 million. However, the number of domestic child workers and children working in the informal sector are much more difficult to estimate because child labour in these two sectors is largely invisible. This invisibility is mainly attributed to the privacy of the domestic sector, the ineffectiveness of legislation, inadequate capacity on the part of the labour inspection unit, paucity of data, cultural values and perceptions as well as lack of public awareness. The problem is compounded by the fact that no legal minimum age of employment has been set in either the informal or the domestic sector. In addition, a lot of Kenyans are not aware of the problem of child labour in general and that of domestic child worker in particular. Children’s work as domestic servants is generally regarded as a normal process of child up-bringing and many families and child employers expect children to work and contribute to their families’ income.Poverty is one of the underlying causes of child labour and one that also interacts with other factors in mutually reinforcing and complex ways and thus the need to argue the links and interplay between some of these factors. The way forward in the combat against child labour is through a public-private partnership of all the actors at all levels and across all sectors because poverty is a multi-sectoral problem and the main sites of invisible child labour are the informal and domestic sectors.To be more effective, sustainable action against invisible child labour should be designed to bring different groups of actors together into a partnership to address the problem and should put a great deal of emphasis on the empowerment of the community, the family and the working children as the central focus of attention and targeted local interventions, particularly in the urban slums. This should be done simultaneously with the promotion of community participation to mobilize local resources for expanding basic social services to poor urban neighbourhoods and increasing access to them by families and individuals.